"No generics, Doctor!" The perspective of general practitioners in two French regions - Béatrice Riner; Adèle Bussy; Jeannie Hélène-Pelage; Nycrees Moueza; Sébastien Lamy; Philippe Carrère (BMC, 2017)
Abstract Background Generic medicines are essential to controlling health expenditures. Their market share is still small in France. The discourse and practices of prescribers may play a major role in their use. The purpose of this study was to explore the knowledge, attitudes and practices of general practitioners (GPs) toward generic medicines in two French regions with the lowest penetration rate of these products. Methods An observational study was carried out from October 2015 to February 2016 in Guadeloupe and Martinique. The first qualitative phase involved a diversified sample of 14 GPs who underwent semi-structured interviews. The second phase involved a random sample of 316 GPs (response rate = 74%) who were administered a structured questionnaire developed from the results of the first phase. Results Seventy-eight percent of the participants defined a generic drug as a drug containing an active substance identical to a brand-name drug, but only 11% considered generic drugs to be equivalent to brand-name drugs, and the same proportion believed that the generic drugs were of doubtful quality. The primary recognized advantage of generic medicines was their lower cost (82%). The main drawbacks cited were the variability of their presentation (44%), the confusion that they caused for some patients (47%), frequent allegations of adverse side effects (37%) and a lack of efficacy (24%), and frequent refusal by patients (26%). Seventy-four percent of the participants stated that they adapted their prescribing practices to the situation, and of this group, 47% prescribed the originator product simply on demand. Conclusion Most surveyed GPs were not hostile towards generic medicines. They were caught between the requirements of health insurance regimes and the opposition of numerous users and suggested that the patient information provided by health authorities should be improved and that drug composition and packaging should be made uniform.